2011
DOI: 10.1073/pnas.1018426108
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-deep sequencing of foraminiferal microbarcodes unveils hidden richness of early monothalamous lineages in deep-sea sediments

Abstract: Deep-sea floors represent one of the largest and most complex ecosystems on Earth but remain essentially unexplored. The vastness and remoteness of this ecosystem make deep-sea sampling difficult, hampering traditional taxonomic observations and diversity assessment. This problem is particularly true in the case of the deep-sea meiofauna, which largely comprises small-sized, fragile, and difficult-to-identify metazoans and protists. Here, we introduce an ultra-deep sequencing-based metagenetic approach to exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
133
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 36 publications
4
133
0
Order By: Relevance
“…Deep-sequencing technologies can create a fuller picture of protistan diversity, as samples can be analysed both in parallel and in depth, leading to quantitatively and qualitatively enlarged taxa lists per sample (Triadó-Margarit & Casamayor 2012, Bates et al 2013. In numerous cases, high-throughput sequencing has shown that protistan diversity has been highly underestimated in the past , Stoeck et al 2010, Lecroq et al 2011. Moreover, such deeper diversity surveys also hold the potential to reveal protistan diversity and distribution patterns among sites and samples that could not be seen so far (Grossmann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Deep-sequencing technologies can create a fuller picture of protistan diversity, as samples can be analysed both in parallel and in depth, leading to quantitatively and qualitatively enlarged taxa lists per sample (Triadó-Margarit & Casamayor 2012, Bates et al 2013. In numerous cases, high-throughput sequencing has shown that protistan diversity has been highly underestimated in the past , Stoeck et al 2010, Lecroq et al 2011. Moreover, such deeper diversity surveys also hold the potential to reveal protistan diversity and distribution patterns among sites and samples that could not be seen so far (Grossmann et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing combination of morphological and DNA sequence analyses in single specimens has revealed, for instance, cryptic species with different distributions and likely dissimilar ecology in marine plankton (Weiner et al, 2012;Ishitani et al, 2014;Santoferrara et al, 2015). Furthermore, the characterization of natural communities by high-throughput sequencing (HTS) is now offering the potential to reveal new distribution patterns based on the detection of rare species and the discovery of novel, atypical taxa that may not be recognized by microscopy, even in some groups with a long tradition of morphological description (Lecroq et al, 2011). At the same time, these conspicuous groups are useful to test known issues of environmental HTS, as parallel morphospecies identification in the microscope helps to differentiate meaningful operational taxonomic units (OTUs based on sequence similarity) from potential HTS errors (for example, Bachy et al, 2013;Santoferrara et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These sequences represent eDNA exported to the seafloor from the plankton. With the recent development of the Planktonic Foraminifera Ribosomal Ref- erence Database (PFR 2 ; Morard et al, 2015), the environmental sequences belonging to planktonic foraminifera in the eDNA libraries generated by Lecroq et al (2011) can now be, for the first time, thoroughly analyzed and assigned to the morphological and cryptic species levels The extensive knowledge on the distribution and abundance of planktonic foraminiferal shells in surface sediments (Kucera et al, 2005) enabled the eDNA data to be directly compared with data derived from classical taxonomy. We thus assess to what extent the eDNA originating from plankton is representative of the source community, which is an essential prerequisite for interpretation of the eDNA archive in the sediment.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study we perform new analysis on eDNA libraries generated by Lecroq et al (2011), which comprise metabarcodes from 31 abyssal sediment samples containing ∼ 78 million foraminiferal sequences derived from the 37f foraminiferal specific barcode of the 18S rDNA. The major portion (> 99 %) of the sequences could be assigned to benthic taxa and their composition was analyzed to unravel the patterns of benthic diversity on the seafloor.…”
Section: Introductionmentioning
confidence: 99%